Method for producing sulfide-based inorganic solid electrolyte material

JP7640632B2Active Publication Date: 2025-03-05FURUKAWA COMPANY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023156361
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-02
Filing Date
2023-09-21
Publication Date
2025-03-05
Estimated Expiration
2040-08-18

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、リチウムイオン伝導性が向上した硫化物系無機固体電解質材料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640632000001
    Figure 0007640632000001
Patent Text Reader

Abstract

To provide a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity.SOLUTION: A method for producing a sulfide-based inorganic solid electrolyte material includes: a process (A) of preparing a glassy-state sulfide-based inorganic solid electrolyte material; and a process (B) of annealing the glassy-state sulfide-based inorganic solid electrolyte material by using heating means, where the process (B) includes: a process (B1) of arranging the glassy-state sulfide-based inorganic solid electrolyte material in a heating space; a process (B2) of annealing the glassy-state sulfide-based inorganic solid electrolyte material arranged inside the heating space while raising the temperature of the heating means from an initial temperature T0 to an annealing temperature T1; and a process (B3) of annealing the glassy-state sulfide-based inorganic solid electrolyte material arranged inside the heating space at the annealing temperature T1, in this order. In the process (B2), a temperature rising rate from the initial temperature T0 to the annealing temperature T1 is 2°C / min. or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a sulfide-based inorganic solid electrolyte material. [Background technology]

[0002] Lithium-ion batteries are generally used as power sources for small portable devices such as mobile phones and laptops, etc. Recently, lithium-ion batteries have also begun to be used as power sources for electric vehicles, power storage, and other devices in addition to small portable devices.

[0003] Lithium ion batteries currently available on the market use electrolytes containing flammable organic solvents. On the other hand, lithium ion batteries in which the electrolyte is changed to a solid electrolyte and the battery is made all-solid (hereinafter also referred to as all-solid-state lithium ion batteries) do not use flammable organic solvents in the battery, and therefore are considered to be superior in terms of manufacturing cost and productivity, with simplified safety devices. As a solid electrolyte material used for such solid electrolytes, for example, a sulfide-based solid electrolyte material is known.

[0004] For example, in Patent Document 1 (JP 2016-27545 A), a peak is observed at 2θ=29.86°±1.00° in X-ray diffraction measurement using CuKα radiation, and Li 2y+3 A sulfide-based solid electrolyte material is described that is characterized by having a composition of PS4 (0.1≦y≦0.175). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-27545 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, although sulfide-based inorganic solid electrolyte materials have excellent electrochemical stability and lithium ion conductivity, their lithium ion conductivity is still low compared to that of electrolyte solutions, and they are not fully satisfactory as solid electrolyte materials. For these reasons, there is a demand for sulfide-based inorganic solid electrolyte materials used in lithium-ion batteries to have electrochemical stability while also exhibiting improved lithium ion conductivity.

[0007] The present invention has been made in view of the above circumstances, and provides a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to achieve the above object, and as a result, have found that a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity can be obtained by annealing a sulfide-based inorganic solid electrolyte material in a glassy state under specific conditions, thereby completing the present invention.

[0009] According to the present invention, A step (A) of preparing a sulfide-based inorganic solid electrolyte material in a glass state; and (B) annealing the sulfide-based inorganic solid electrolyte material in a glassy state using a heating means; The step (B) includes, in this order, a step (B1) of placing the sulfide-based inorganic solid electrolyte material in a heating space, a step (B2) of annealing the sulfide-based inorganic solid electrolyte material in a glassy state placed in the heating space while raising the temperature of the heating means from an initial temperature T0 to an annealing temperature T1, and a step (B3) of annealing the sulfide-based inorganic solid electrolyte material in a glassy state placed in the heating space at the annealing temperature T1; There is provided a method for producing a sulfide-based inorganic solid electrolyte material, wherein in the step (B2), the rate of temperature rise from the initial temperature T0 to the annealing temperature T1 is 2° C. / min or more. Effect of the Invention

[0010] According to the present invention, it is possible to provide a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described. Note that a numerical range of "A to B" means A or more and B or less unless otherwise specified.

[0012] The method for producing a sulfide-based inorganic solid electrolyte material according to the present embodiment includes a step (A) of preparing a sulfide-based inorganic solid electrolyte material in a glassy state, and a step (B) of annealing the sulfide-based inorganic solid electrolyte material in the glassy state using a heating means, and the step (B) includes a step (B1) of placing the sulfide-based inorganic solid electrolyte material in a heating space, a step (B2) of annealing the sulfide-based inorganic solid electrolyte material in the glassy state placed in the heating space while increasing the temperature of the heating means from an initial temperature T0 to an annealing temperature T1, and a step (B3) of annealing the sulfide-based inorganic solid electrolyte material in the glassy state placed in the heating space at the annealing temperature T1, in this order, and in the step (B2), the heating rate from the initial temperature T0 to the annealing temperature T1 is 2° C. / min or more.

[0013] According to the method for producing a sulfide-based inorganic solid electrolyte material according to this embodiment, it is possible to obtain a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity.

[0014] The sulfide-based inorganic solid electrolyte material obtained by the method for producing a sulfide-based inorganic solid electrolyte material according to this embodiment contains Li, P and S as constituent elements. In addition, from the viewpoint of further improving the lithium ion conductivity, electrochemical stability, stability in moisture and air, ease of handling, and the like, the sulfide-based inorganic solid electrolyte material according to this embodiment has a molar ratio Li / P of the Li content to the P content in the sulfide-based inorganic solid electrolyte material of preferably 1.0 or more and 10.0 or less, more preferably 1.0 or more and 5.0 or less, even more preferably 2.0 or more and 4.5 or less, even more preferably 3.0 or more and 4.2 or less, even more preferably 3.1 or more and 4.0 or less, and particularly preferably 3.2 or more and 3.8 or less. In addition, the molar ratio S / P of the S content to the P content is preferably 1.0 or more and 10.0 or less, more preferably 2.0 or more and 6.0 or less, even more preferably 3.0 or more and 5.0 or less, still more preferably 3.5 or more and 4.5 or less, and particularly preferably 3.8 or more and 4.2 or less. Here, the contents of Li, P and S in the sulfide-based inorganic solid electrolyte material according to this embodiment can be determined by, for example, ICP emission spectrometry or X-ray analysis.

[0015] The sulfide-based inorganic solid electrolyte material according to this embodiment can be used in any application requiring lithium ion conductivity. In particular, the sulfide-based inorganic solid electrolyte material according to this embodiment is preferably used in a lithium ion battery. More specifically, it is used in a positive electrode active material layer, a negative electrode active material layer, an electrolyte layer, etc. in a lithium ion battery. Furthermore, the sulfide-based inorganic solid electrolyte material according to this embodiment is preferably used in a positive electrode active material layer, a negative electrode active material layer, a solid electrolyte layer, etc. constituting an all-solid-state lithium ion battery, and is particularly preferably used in a solid electrolyte layer constituting an all-solid-state lithium ion battery. An example of an all-solid-state lithium ion battery using the sulfide-based inorganic solid electrolyte material according to this embodiment is one in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order.

[0016] Each step will be described in detail below.

[0017] (Process (A)) First, a sulfide-based inorganic solid electrolyte material in a glass state is prepared. A sulfide-based inorganic solid electrolyte material in a glassy state can be obtained, for example, by preparing a mixture containing lithium sulfide and phosphorus sulfide, and then mechanically treating the mixture to vitrify the raw materials lithium sulfide and phosphorus sulfide while causing a chemical reaction.

[0018] The mixture containing lithium sulfide and phosphorus sulfide can be obtained, for example, by mixing the respective raw materials in a predetermined molar ratio so that the target sulfide-based inorganic solid electrolyte material has a desired composition ratio. Here, the mixing ratio of each raw material in the mixture is adjusted so that the resulting sulfide-based inorganic solid electrolyte material has a desired composition ratio. The method for mixing the raw materials is not particularly limited as long as it can mix the raw materials uniformly. For example, the raw materials can be mixed using a ball mill, a bead mill, a vibration mill, an impact grinding device, a mixer (a pug mixer, a ribbon mixer, a tumbler mixer, a drum mixer, a V-type mixer, etc.), a kneader, a two-shaft kneader, an airflow grinder, etc. The mixing conditions when mixing the raw materials, such as the stirring speed, processing time, temperature, reaction pressure, and gravitational acceleration applied to the mixture, can be appropriately determined depending on the processing amount of the mixture.

[0019] The lithium sulfide used as the raw material is not particularly limited, and commercially available lithium sulfide may be used, or lithium sulfide obtained by reacting lithium hydroxide with hydrogen sulfide may be used. From the viewpoint of obtaining a high-purity sulfide-based inorganic solid electrolyte material and suppressing side reactions, it is preferable to use lithium sulfide with few impurities. In this embodiment, the lithium sulfide includes lithium polysulfide. Li2S is preferable as the lithium sulfide.

[0020] The phosphorus sulfide used as the raw material is not particularly limited, and commercially available phosphorus sulfides (e.g., P2S5, P4S3, P4S7, P4S5, etc.) can be used. From the viewpoint of obtaining a high-purity sulfide-based inorganic solid electrolyte material and from the viewpoint of suppressing side reactions, it is preferable to use phosphorus sulfide with few impurities. As the phosphorus sulfide, P2S5 is preferable.

[0021] Lithium nitride may also be used as a raw material. Here, since the nitrogen in lithium nitride is discharged into the system as N2, by using lithium nitride as a raw material, it becomes possible to increase only the Li composition in a sulfide-based inorganic solid electrolyte material that contains Li, P, and S as constituent elements. The lithium nitride according to the present embodiment is not particularly limited, and may be commercially available lithium nitride (e.g., Li3N, etc.), or may be obtained by reacting metallic lithium (e.g., Li foil) with nitrogen gas. From the viewpoint of obtaining a high-purity solid electrolyte material and suppressing side reactions, it is preferable to use lithium nitride with few impurities.

[0022] Next, the mixture containing lithium sulfide and phosphorus sulfide is mechanically treated to vitrify the raw materials lithium sulfide and phosphorus sulfide while causing a chemical reaction, thereby obtaining a sulfide-based inorganic solid electrolyte material in a glassy state. The mechanical treatment herein is a treatment in which two or more inorganic compounds are mechanically collided with each other to cause a chemical reaction and thereby vitrification, and examples thereof include mechanochemical treatment. Furthermore, from the viewpoint of easily realizing an environment in which moisture and oxygen are removed to a high degree in the vitrification step, the mechanical treatment is preferably carried out in a dry manner, and a dry mechanochemical treatment is more preferable. By using the mechanochemical treatment, the raw materials can be mixed while being pulverized into fine particles, so that the contact area of ​​the raw materials can be increased, which promotes the reaction of the raw materials, and thus makes it possible to more efficiently obtain a sulfide-based inorganic solid electrolyte material in a glassy state.

[0023] Here, mechanochemical treatment is a method of vitrification while applying mechanical energy such as shear force, impact force, or centrifugal force to the target composition. Apparatuses for vitrification by mechanochemical treatment include crushing and dispersing machines such as ball mills, bead mills, vibration mills, turbo mills, mechanofusion, disk mills, and roll mills; rotary impact crushing machines consisting of a mechanism combining rotation (shear stress) and impact (compressive stress) represented by rock drills, vibration drills, impact drivers, etc.; and high-pressure gliding rolls. Among these, ball mills and bead mills are preferred from the viewpoint of efficiently generating very high impact energy, and ball mills are particularly preferred. In addition, from the viewpoint of excellent continuous productivity, roll mills; rotary impact crushing machines consisting of a mechanism combining rotation (shear stress) and impact (compressive stress) represented by rock drills, vibration drills, impact drivers, etc.; and high-pressure gliding rolls, etc. are preferred.

[0024] In addition, the mechanochemical treatment is preferably carried out in an inert atmosphere, which can suppress reactions between the sulfide-based inorganic solid electrolyte material and water vapor, oxygen, and the like. The inert atmosphere means a vacuum atmosphere or an inert gas atmosphere. In the inert atmosphere, the dew point is preferably -50°C or less, more preferably -60°C or less, to avoid contact with moisture. The inert gas atmosphere means an atmosphere of an inert gas such as argon gas, helium gas, or nitrogen gas. These inert gases are preferably as high in purity as possible to prevent impurities from being mixed into the product. The method of introducing the inert gas into the mixed system is not particularly limited as long as the mixed system is filled with an inert gas atmosphere, and examples of the method include a method of purging the inert gas and a method of continuously introducing a constant amount of the inert gas.

[0025] The mixing conditions, such as the rotation speed, processing time, temperature, reaction pressure, and gravitational acceleration applied to the mixture, when mechanically processing the mixture containing lithium sulfide and phosphorus sulfide, can be appropriately determined depending on the type and processing amount of the mixture. In general, the faster the rotation speed, the faster the glass production rate, and the longer the processing time, the higher the conversion rate to glass. Typically, when X-ray diffraction analysis is performed using CuKα radiation as the radiation source, if the diffraction peaks derived from the raw materials disappear or decrease, it can be determined that the mixture has been vitrified and a sulfide-based inorganic solid electrolyte material in a glassy state has been obtained.

[0026] Here, in the process of vitrifying the mixture containing lithium sulfide and phosphorus sulfide, the lithium ion conductivity by the AC impedance method under the measurement conditions of 27.0 °C, applied voltage of 10 mV, and measurement frequency range of 0.1 Hz to 7 MHz is 0.5 × 10 -4 S cm -1 More than 1.0×10 -4 S cm -1 It is preferable to carry out the mechanical treatment until the above-mentioned temperature is reached, whereby a sulfide-based inorganic solid electrolyte material having even more excellent lithium ion conductivity can be obtained.

[0027] (Process (B)) Next, the sulfide-based inorganic solid electrolyte material in a glass state is annealed using a heating means. In the method for producing a sulfide-based inorganic solid electrolyte material according to the present embodiment, the sulfide-based inorganic solid electrolyte material in a glassy state is annealed to crystallize at least a part of the sulfide-based inorganic solid electrolyte material in the glassy state. That is, by heating the sulfide-based inorganic solid electrolyte material in the glassy state, at least a part of the sulfide-based inorganic solid electrolyte material in the glassy state is crystallized to obtain a sulfide-based inorganic solid electrolyte material in a glass ceramic state (also called crystallized glass). This can improve the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material.

[0028] Step (B) includes a step (B1) of placing a sulfide-based inorganic solid electrolyte material in a glassy state in a heating space, a step (B2) of annealing the sulfide-based inorganic solid electrolyte material in a glassy state placed in the heating space while raising the temperature of the heating means from the initial temperature T0 to the annealing temperature T1, and a step (B3) of annealing the sulfide-based inorganic solid electrolyte material in a glassy state placed in the heating space at the annealing temperature T1, in this order, and in step (B2), the heating rate from the initial temperature T0 to the annealing temperature T1 is 2°C / min or more, preferably 3°C / min or more, more preferably 5°C / min or more, and even more preferably 7°C / min or more. The upper limit of the heating rate is not particularly limited, but may be, for example, 1000°C / min or less, 800°C / min or less, or 600°C / min or less.

[0029] By setting the heating rate in step (B2) to be equal to or higher than the lower limit, the lithium ion conductivity of the resulting sulfide-based inorganic solid electrolyte material in a glass ceramic state can be improved. Although the reason for this is not clear, the following reason is presumed. First, when the heating rate is equal to or higher than the lower limit, it is believed that the generation of crystal nuclei is reduced, and a sulfide-based inorganic solid electrolyte material in a glass-ceramic state with fewer grain boundaries is obtained. It is believed that the fewer the grain boundaries, the smaller the resistance of the grain boundaries is, and the better the lithium ion conductivity is. For the above reasons, it is believed that by setting the heating rate to be equal to or higher than the lower limit, it is possible to obtain a sulfide-based inorganic solid electrolyte material in a glass-ceramic state with improved lithium ion conductivity.

[0030] Examples of the heating means include convection heating, conductive heating, radiation heating, etc. These heating means may be used alone or in combination of two or more. Conductive heat transfer heating is a method of contacting a sulfide-based inorganic solid electrolyte material with a high-temperature object and heating it by thermal conduction, and examples of devices for conducting conductive heat transfer heating include a hot plate heater, a heating roll, a carbon crucible, etc. Here, conductive heat transfer heating using a carbon crucible is a method of, for example, placing a sulfide-based inorganic solid electrolyte material in a carbon crucible, heating the carbon crucible with an infrared heater or an infrared lamp, and heating the sulfide-based inorganic solid electrolyte material with the heat of the heated carbon crucible. Radiation heat transfer heating is a method of heating a high-temperature object by absorbing energy emitted as electromagnetic waves into a lithium material. Examples of devices that perform radiation heat transfer heating include infrared heaters and infrared lamps. Among these, conductive heating is preferred because it allows the sulfide-based inorganic solid electrolyte material to be effectively annealed in a short period of time.

[0031] The initial temperature T0 is the temperature of the heating means when the sulfide-based inorganic solid electrolyte material in a glassy state is placed in the heating space, and is, for example, 0°C or higher and 100°C or lower, preferably 10°C or higher and 50°C or lower, and more preferably 15°C or higher and 40°C or lower. Here, in the method for producing a sulfide-based inorganic solid electrolyte material according to this embodiment, the embodiment does not include a case in which a glass-state sulfide-based inorganic solid electrolyte material is placed and annealed after the heating space reaches the annealing temperature T1.

[0032] The annealing temperature T1 is not particularly limited as long as it is a temperature at which crystallization can be sufficiently promoted. For example, from the viewpoint of effectively promoting crystallization while suppressing thermal decomposition of the sulfide-based inorganic solid electrolyte material in a glassy state, the annealing temperature T1 is preferably in the range of 220°C or higher and 500°C or lower, more preferably in the range of 230°C or higher and 400°C or lower, more preferably in the range of 240°C or higher and 350°C or lower, and even more preferably in the range of 250°C or higher and 350°C or lower. Here, the initial temperature T0 and the annealing temperature T1 are the temperatures of the heating means, and in the case of convection heating and radiation heating, they indicate the atmospheric temperatures of the heating space, and in the case of conduction heating, they indicate the surface temperatures of the high-temperature object.

[0033] In steps (B2) and (B3), the total time for the annealing treatment is not particularly limited as long as it is a time that allows a sulfide-based inorganic solid electrolyte material in a desired glass ceramic state to be obtained, but is, for example, in the range of 1 minute to 24 hours, preferably in the range of 0.5 hours to 8 hours, and more preferably in the range of 1 hour to 3 hours. The conditions such as temperature and time during such annealing treatment can be appropriately adjusted to optimize the properties of the sulfide-based inorganic solid electrolyte material.

[0034] In the method for producing a sulfide-based inorganic solid electrolyte material according to the present embodiment, it is preferable that the heating space in at least step (B2) and step (B3) is an inert gas atmosphere, which can prevent deterioration (e.g., oxidation) of the sulfide-based inorganic solid electrolyte material. Examples of the inert gas used include argon gas, helium gas, and nitrogen gas. These inert gases are preferably as high in purity as possible to prevent impurities from being mixed into the product, and the dew point is preferably -30°C or less, more preferably -50°C or less, and particularly preferably -60°C or less to avoid contact with moisture. The method of introducing the inert gas into the heating space is not particularly limited as long as the heating space is filled with an inert gas atmosphere, and examples of the method include a method of purging the inert gas and a method of continuously introducing a constant amount of the inert gas.

[0035] In addition, whether or not at least a portion of the sulfide-based inorganic solid electrolyte material has crystallized can be determined, for example, by whether or not a new crystal peak is generated in a spectrum obtained by X-ray diffraction using CuKα radiation as a radiation source.

[0036] (Crushing, classifying, or granulating process) In the method for producing a sulfide-based inorganic solid electrolyte material according to this embodiment, a step of pulverizing, classifying, or granulating the obtained sulfide-based inorganic solid electrolyte material may be further performed as necessary. For example, a sulfide-based inorganic solid electrolyte material having a desired particle size can be obtained by pulverizing to obtain fine particles, and then adjusting the particle size by a classification operation or a granulation operation. The above-mentioned pulverizing method is not particularly limited, and known pulverizing methods such as a mixer, airflow pulverization, a mortar, a rotary mill, and a coffee mill can be used. The above-mentioned classification method is also not particularly limited, and known methods such as a sieve can be used. The pulverization or classification is preferably carried out in an inert gas atmosphere or a vacuum atmosphere, since this can prevent contact with moisture in the air.

[0037] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. The present invention is not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. EXAMPLES

[0038] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.

[0039] <Evaluation method> First, the evaluation methods in the following Examples and Comparative Examples will be described.

[0040] (1) Measurement of lithium ion conductivity The lithium ion conductivity of the sulfide-based inorganic solid electrolyte materials obtained in the examples and comparative examples was measured by an AC impedance method. The lithium ion conductivity was measured using a potentiostat / galvanostat SP-300 manufactured by Biologic Corp. The sample size was 9.5 mm in diameter and 1.2 to 2.0 mm in thickness, and the measurement conditions were an applied voltage of 10 mV, a measurement temperature of 27.0°C, a measurement frequency range of 0.1 Hz to 7 MHz, and a Li foil electrode. Here, as the sample for measuring lithium ion conductivity, a plate-shaped sulfide-based inorganic solid electrolyte material having a diameter of 9.5 mm and a thickness of 1.2 to 2.0 mm was used, which was obtained by pressing 150 mg of the powdered sulfide-based inorganic solid electrolyte material obtained in the examples and comparative examples at 270 MPa for 10 minutes using a pressing device.

[0041] (2) Measurement of the composition ratio of sulfide-based inorganic solid electrolyte materials Using an ICP optical emission spectrometer (Seiko Instruments Inc., SPS3000), measurements were performed by ICP optical emission spectroscopic analysis to determine the mass percentages of Li, P, and S in the sulfide-based inorganic solid electrolyte materials obtained in the examples and comparative examples, and the molar ratios of each element were calculated based on the results.

[0042] <Example 1> (1) Preparation of sulfide-based inorganic solid electrolyte materials A sulfide-based inorganic solid electrolyte material was prepared by the following procedure. The raw materials used were Li2S (manufactured by Furukawa Co., Ltd., purity 99.9%), P2S5 (manufactured by Kanto Chemical Co., Ltd.), and Li3N (manufactured by Furukawa Co., Ltd.). First, a rotary blade grinder and an alumina pot (internal volume 400 mL) were placed in the glove box, and then high-purity dry argon gas (H2O<1 ppm, O2<1 ppm) obtained through a gas purification system was injected into the glove box and vacuum degassed three times. Next, in a glove box, a rotary blade grinder (rotation speed 18,000 rpm) was used to mix a total of 5 g of Li2S powder, P2S5 powder, and Li3N powder (Li2S:P2S5:Li3N = 71.1:23.7:5.3 (mol%)) (10 times of mixing for 10 seconds and leaving for 10 seconds (cumulative mixing time: 100 seconds)), to prepare a raw material inorganic composition.

[0043] Next, the raw material inorganic composition and 500 g of ZrO2 balls having a diameter of 10 mm were placed in an alumina pot (inner volume: 400 mL) in the glove box, and the pot was sealed. Next, the alumina pot was taken out of the glove box, and the alumina pot was attached to a ball mill placed in an atmosphere of dry air introduced through a membrane air dryer, and mechanochemical treatment was carried out at 120 rpm for 500 hours to vitrify the raw material inorganic composition. After every 48 hours of mixing, the powder on the inner wall of the pot was scraped off in the glove box, and after sealing, milling was continued in a dry air atmosphere. Next, an alumina pot was placed in the glove box, and the obtained powder (0.35 g) was transferred from the alumina pot to a carbon crucible. The carbon crucible was heated with a tabletop lamp heating device installed in the glove box, and the temperature of the carbon crucible was increased to 260° C. Here, the initial temperature T0 of the carbon crucible was 23° C., and the temperature increase rate was 9° C. / min. The annealing treatment was performed for 2 hours from the start of heating the carbon crucible. The temperature of the carbon crucible was measured by contacting a thermocouple with the bottom surface on the outside of the carbon crucible. The obtained sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 The results are shown in Table 1.

[0044] <Examples 2 to 4 and Comparative Example 1> A sulfide-based inorganic solid electrolyte material (Li) in a glass ceramic state was prepared in the same manner as in Example 1, except that the heating rate of the carbon crucible was changed as shown in Table 1. 10 P3S 12 The lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material in a glass ceramic state was measured. The results are shown in Table 1.

[0045] <Examples 5 and 6> A sulfide-based inorganic solid electrolyte material (Li) in a glass ceramic state was prepared in the same manner as in Example 1, except that the heating rate and annealing temperature of the carbon crucible were changed as shown in Table 1. 10 P3S 12The lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material in a glass ceramic state was measured. The results are shown in Table 1.

[0046] [Table 1]

[0047] It can be seen that the method for producing a sulfide-based inorganic solid electrolyte material of the example in which the temperature rise rate is 2° C. / min or more produces a sulfide-based inorganic solid electrolyte material with high ionic conductivity in a shorter time. From the above, it can be understood that according to the method for producing a sulfide-based inorganic solid electrolyte material according to this embodiment, it is possible to obtain a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity.

[0048] This application claims priority based on Japanese Patent Application No. 2019-182311, filed on October 2, 2019, the disclosure of which is incorporated herein in its entirety.

Claims

1. A step (A) of preparing a sulfide-based inorganic solid electrolyte material in a glass state; and (B) annealing the sulfide-based inorganic solid electrolyte material in a glassy state using a heating means; The step (B) includes a step (B1) of placing the sulfide-based inorganic solid electrolyte material in a glass state in a heating space, and a step of setting the temperature of the heating means to an initial temperature T 0 to annealing temperature T 1 a step (B2) of annealing the sulfide-based inorganic solid electrolyte material in a glass state placed in the heating space while raising the temperature to the annealing temperature T 1 and (B3) annealing the resultant product in this order. In the step (B2), the initial temperature T 0 to the annealing temperature T 1 The heating rate is 2° C. / min or more, The annealing temperature T 1 is 220° C. or more and 260° C. or less, The heating means includes conductive heat transfer heating; The sulfide-based inorganic solid electrolyte material in a glassy state is prepared by preparing a mixture containing lithium sulfide and phosphorus sulfide, and mechanically treating the mixture; The method for producing a sulfide-based inorganic solid electrolyte material, wherein the mechanical treatment is performed by a dry method.

2. The method for producing a sulfide-based inorganic solid electrolyte material according to claim 1, The method for producing a sulfide-based inorganic solid electrolyte material, wherein the heating space in the step (B2) and the step (B3) is an inert gas atmosphere.

3. The method for producing a sulfide-based inorganic solid electrolyte material according to claim 1 or 2, The method for producing a sulfide-based inorganic solid electrolyte material, wherein a total time for performing the annealing treatment in the step (B2) and the step (B3) is 0.5 hours or more and 24 hours or less.

4. The method for producing a sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 3, The initial temperature T 0 The method for producing a sulfide-based inorganic solid electrolyte material,

5. The method for producing a sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 4, The sulfide-based inorganic solid electrolyte material contains Li, P and S as constituent elements.

6. The method for producing a sulfide-based inorganic solid electrolyte material according to claim 5, A method for producing a sulfide-based inorganic solid electrolyte material, wherein a molar ratio (Li / P) of the Li content to the P content in the sulfide-based inorganic solid electrolyte material is 1.0 or more and 10.0 or less, and a molar ratio (S / P) of the S content to the P content is 1.0 or more and 10.0 or less.

Citation Information

Patent Citations

  • Preparation method of sulfide solid electrolyte

    CN110165293A

  • Method of manufacturing crystallized sulfide solid electrolyte material

    JP2010218827A

  • Sulfide solid electrolytic material, battery, and method for manufacturing sulfide solid electrolytic material

    JP2016027545A

  • JPP7355837B